Creative tourism special issue: foreword - Marques, João Filipe (2019)
This Tourism and Management Studies Special Issue on Creative Tourism is born under the scope of a very original project: the CREATOUR - Creative Tourism Destination Development in Small Cities and Rural Areas. The CREATOUR project is the first action-research project in Portugal whose objectives are to study and to stimulate the creative tourism initiatives in small places and rural areas. CREATOUR is an incubator/demonstration and multidisciplinary research initiative, supporting collaborative research processes involving five Portuguese research centres working with a range of cultural/creative organisations and other stakeholders located in small cities across Portugal in the Norte, Centro, Alentejo and Algarve regions.